Combination of Murottal Al-Qur'an, Asmaul Husna, Dhikr and Aromatherapy "Muasda" on Blood Pressure, Alpha Amylase Levels and Spiritual Wellbeing in Hypertension Clients - Siti Rizki Amalia; Sudirman, Sudirman; Pujiastuti, Rr. Sri Endang; Suwondo, Ari; Arwani, Arwani (Window of Health : Jurnal Kesehatan, 2023)
Hypertension is a non-communicable disease, but prevention is needed because it risks causing other body organs to be damaged organs, either directly or indirectly. The combination of “muasda” causes relaxation, giving derivatives in blood pressure, and alpha-amylase levels, and increasing spiritual well-being. This study aims to determine the effect of the muasda combination on blood pressure, alpha-amylase levels, and spiritual well-being in hypertensive clients. This research is a quasi-experiment using pre-test and post-test with a control group design. The number of samples in this study was 62 respondents divided into two groups, namely the intervention and control groups. In taking the sample, the researcher used simple random sampling. The intervention in this study was a muasda combination, given for seven consecutive days with a time of administration of 45 minutes. In the intervention group, respondents will receive a muasda combination and amlodipine. The control group received amlodipine from the public health center. In the intervention group, the mean decrease in systolic blood pressure was 35 mmHg or 11.7% (p = 0.000). The mean decrease in diastolic blood pressure was 24 mmHg or 8% (p = 0.000). The average decrease in alpha-amylase levels was 26.58 or 19% (p = 0.000). The average increase in spiritual well-being scores was 36.94 or 32% (p = 0.000). The muasda combination reduces blood pressure and alpha-amylase levels and increases spiritual well-being in hypertensive clients.